Study on Varietal Replacement Rate of Groundnut in Saurashtra Region of India - Shanmuka, Adupa; N.B.Jadav,; T.N.S.S Srivani,; Krimpal Khunt, (Indian Journal of Extension Education, 2024)
The study conducted during 2024 investigated the dynamics of Variety Replacement Rate (VRR) in groundnut cultivation in Gujarat, India, which contributes significantly to the country's oilseed production. The study encompasses 180 farmers from three districts in the Saurashtra region, where 40.5% of the nation's groundnut production originates. The study analyzed the extent of the VRR which states that around 41.11% of the respondents had replaced variety every 3-5 years followed by 30% had no replacement from 5 years and the remaining 28.89 % of the respondents had replaced variety for every 2 years. The extent of VRR is influenced by gender, livestock possession, access to credit, occupation, risk orientation, innovativeness, and extension contact. Concerning the perception of farmers towards varietal replacement rate (VRR), 45% of respondents exhibited a neutral perception, followed by 27.78% having a favorable and 27.22% having an unfavorable level of perception towards the varietal replacement rate, emphasizing the need for interventions. Occupation, innovativeness, training received, and awareness significantly influence VRR perception. There is a positive and highly significant relationship between perception towards VRR and the extent of VRR at a 1% significance level with a chi-square value of 22.32.